Prosiding Temu Ilmiah Geriatri 2002 : Penatalaksanaan Pasien Geriatri/ Usia Lanjut - [Tidak Terdaftar] (Fak. Kedokteran UI, 2002)
Prosiding Temu Ilmiah Geriatri 2002 : Penatalaksanaan Pasien Geriatri / Usia Lanjut